Characteristics of local development planning from the perspective of planning documents referring to selected tourist communes = Cechy planowania rozwoju lokalnego w świetle dokumentów planistycznych wybranych gmin turystycznych - Rapacz, Andrzej; Jeremen, Daria E. (Zielona Góra: Faculty of Economics and Management Press)
Local development planning (including the preparation of planning documents) as well as undertaking initiatives and tasks supporting local development (resulting from planning documents) play the key role in local development steering process. The objective of the hereby paper is to analyze planning documents prepared for the selected territorial self-government units (four tourism oriented communes located in Lower Silesia region) in relation to strategic planning qualities identifi cation in particular communes and referring these qualities to the conditions of effective strategic planning (discussed in literature on public management).
Keywords: rozwój lokalny; planowanie strategiczne; zarządzanie publiczne; gmina turystyczna; local development; strategic planning; public management; tourist commune